Constitutional and administrative law - Bradley, A. W. (Anthony Wilfred) (Pearson Education Limited, 2022)
"This edition has been prepared in highly charged circumstances, in which one of us - CJSK - has been involved professionally in litigation and/or providing advice on a range of issues covering both Brexit and Covid-19. We emphasise that all commentary on the politically controversial constitutional developments in the pages that follow is an expression of our personal views for the purpose of setting out the law as we understand it to be. The same is true of our discussion of the case law".